Decreased charge transport distance by titanium mesh-membrane assembly for flow-electrode capacitive deionization with high desalination performance. (1st November 2019) - Yang, Fan; Ma, Junjun; Zhang, Xudong; Huang, Xia; Liang, Peng
Abstract: This study employed a titanium mesh-membrane assembly (MMA) as the current collector in flow-electrode capacitive deionization (FCDI) device (designated as M-FCDI), and obtained a much reduced charge transport distance as compared to traditional FCDI with plate-shaped current collectors located far from the exchange membrane. The average salt removal rate of M-FCDI was greatly improved by 76% under 10 wt% carbon content than the control experiment with graphite plate as current collector, and the charge efficiency remained over 75% even under low carbon loading. This improvement was attributed to the reduced resistance as revealed by electrochemical impedance spectroscopy tests. Further investigation on FCDI's performance with different specifications of titanium meshes showed that the implementation of MMA could provide a larger effective electron transfer area, which would lead to better desalting performance. Graphical abstract: Image 1 Highlights: Titanium mesh-membrane assembly (MMA) as current collector in FCDI. Largely reduced charge transport distance with MMA than graphite plate. Much increased salt removal rate up to 75% attributing to smaller cell resistance. Stable operation over 24 h of FCDI with MMA and with lower energy consumption.